Acrylic substrate based low profile wearable button antenna with FSS layer for WLAN and Wi‐Fi applications. Issue 5 (May 2015) - Mandal, Bappaditya; Chatterjee, Ayan; Parui, Susanta Kumar
ABSTRACT: In this letter, a low profile circularly polarized wearable antenna with the appearance of a button on clothing for Wi‐Fi and WLAN applications is presented. The radiating elements of the antenna are made of copper sheet while a transparent acrylic fiber sheet material is used as substrate and fed by a coaxial line through the ground plane. The proposed antenna is simulated by Ansoft high frequency structure synthesis finite element method‐based (HFSS FEM)‐based EM simulator and has been optimized to operate within the Wi‐Fi and WLAN frequency bands (5250–5850 MHz) with center frequency of 5.25 GHz. A split ring‐shaped slot‐based frequency selective surface (FSS) is designed to enhance the gain of the proposed antenna. The peak gain of the antenna is found to increase from the conventional antenna gain of 2.1 to 5.1 dBi with the superstrate along with a bandwidth enhancement of 290 MHz. The composite FSS antenna is fabricated and the maximum measured gain of 5.1 dBi matches well with theoretical value. The antenna gets miniaturized around 34% by the slits with its circular polarization characteristic well maintained. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1033–1038, 2015